Evaluation of Subsidized Fertilizer Distribution to Corn Farmers in Ogan Komering Ulu Regency - Sahroni, Sahroni; Munajat, Munajat; Sari, Yunita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
This study reviewed the Evaluation of Subsidized Fertilizer Distribution in Corn Farmers in Ogan Komering Ulu Regency, South Sumatra Province. This research aims to analyze the distribution of subsidized fertilizer from producers to farmers of corn crops whether it is following the applicable rules, and to analyze the constraints in the distribution of subsidized fertilizer to corn crop farmers in Ogan Komering Ulu Regency, South Sumatra Province. The research method used is the survey method. The respondents of the study were corn farmers in Ogan Komering Ulu Regency as many as 105 people. Data analysis uses quantitative descriptive analysis techniques with the help of Likers Approximation by using scores on each question item in the questionnaire by making the highest answer to the highest answer